THE DETERMINATION OF THE OUTSIDE MOLD DIMENSION FOR OPTIMIZATION OF THE CLAMPING FORCE OF THE PLASTIC INJECTION MACHINE - Puji Basuki; Ratih Setyaningrum; Muhammad Bagus Laroybafih; Suwantri - (Jurnal Pendidikan Teknik Mesin, 2025)
Injection molding is a popular method that is used to make plastic products due to high productivity, efficiency, and manufacturability. This paper presents the effect of the mold outside dimension on a suitable injection molding machine. It is to capacity in relation to production cost. This research is important as a guide for determining the outer dimensions of the mold to suit the machine being used. The smallest size isn't necessarily the most efficient, as there are minimum dimensions that can be used. The research included calculations for product weight, cycle time, tie bar distance, and minimum mold height. The compatibility between the injection machine used and the mold's outer dimensions is crucial. In this research, the mold height needs to be increased from the previously designed smallest dimensions.